2016
DOI: 10.14267/cjssp.2016.01.01
|View full text |Cite
|
Sign up to set email alerts
|

The quality of inter- and intra-ethnic friendships among roma and non-roma students in Hungary

Abstract: In this paper I compare the quality of inter-and intra-ethnic friendships. Previous studies suggest that interethnic friendships are less likely to be characterized by closeness and intimacy than friendships between same-ethnic peers. I analyze data from a Hungarian panel study conducted among Roma and non-Roma Hungarian secondary school students. The analysis of 13 classes shows that interethnic friendship nominations are indeed less often characterized by co-occurring trust, perceptions of helpfulness, or jo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…(Lena,12,F,Poland) Layering different aspects of friendship with the fluid medium of salt opened up alternative expressive channels, providing a soothing sensory experience during this activity. A hierarchical pattern of perceived trust levels within friendships emerged in which IEI friendships typically achieved the highest positions, echoing the ranking of Roma friendships in Kisfalusi (2016) Well I tell Assia everything, like everything I know she knows, like even my passwords cos I totally trust her. (Rania,12,F,Algeria) The journaling data provided more detailed evidence of a perceived greater depth of loyalty and trust within IEI friendships, demonstrating the inherent suitability of this medium for more in-depth disclosures and experiential self-validation (Baraitser, 2014).…”
Section: Loyalty and Trust Within Iei Friendshipsmentioning
confidence: 91%
“…(Lena,12,F,Poland) Layering different aspects of friendship with the fluid medium of salt opened up alternative expressive channels, providing a soothing sensory experience during this activity. A hierarchical pattern of perceived trust levels within friendships emerged in which IEI friendships typically achieved the highest positions, echoing the ranking of Roma friendships in Kisfalusi (2016) Well I tell Assia everything, like everything I know she knows, like even my passwords cos I totally trust her. (Rania,12,F,Algeria) The journaling data provided more detailed evidence of a perceived greater depth of loyalty and trust within IEI friendships, demonstrating the inherent suitability of this medium for more in-depth disclosures and experiential self-validation (Baraitser, 2014).…”
Section: Loyalty and Trust Within Iei Friendshipsmentioning
confidence: 91%
“…Our study contributes to the literature in several ways. First, we show important determinants of friendship and hostility relations among Roma and non-Roma students, an understudied topic despite the large size and severe disadvantages of the Roma minority in many Eastern European countries (see Boda and Néray, 2015;Kisfalusi, 2016;Lőrincz, 2016 for exceptions, all from very recent years). Second, we show evidence of the association between networks and academic achievement as well as its interaction with exposure.…”
Section: Introductionmentioning
confidence: 88%
“…Studies have identified both similarities as well as differences in friendship quality between ethnic in-and out-group friendships. In-group friendships have been found to be characterized by greater closeness, mutual trust and perceptions of helpfulness (Kisfalusi, 2016) and more shared activities (Kao & Joyner, 2004). Conversely, some studies have found no differences at all (Lessard et al, 2019; Alvarez Valdivia et al, 2016; McDonald et al, 2013; Reinders & Mangold, 2005).…”
Section: Introductionmentioning
confidence: 99%